Synthesis of Sparsomycin via Regioselective Oxidation of Disulfide Intermediate Employing Titanium–Mandelate Complex - Kano, Taichi; Hata, Shogo; Senoh, Shizuku; Gotoh, Nina; Okamoto, Ryusuke; Kato, Yamato; Matsugi, Masato (Synlett, 2025)
The total synthesis of sparsomycin, a natural bioactive compound with both antitumor and antibiotic activities, was achieved using a titanium–mandelate complex that regioselectively oxidizes one of the sulfide moieties in a synthetic intermediate containing a disulfide structure. This oxidation process exhibited a regioselectivity of 73:27, preferentially oxidizing the sterically hindered sulfur atom at the desired internal position. Using the single diastereomer of the purified monosulfoxide, the synthesis of sparsomycin was then accomplished.
Keywords: sparsomycin; disulfide; oxidation; titanium; mandelic acid; complex